2017
DOI: 10.29312/remexca.v8i8.707
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico de la situación actual de la escama blanca del mango

Abstract: El mango es el frutal de mayor importancia socioeconómica del estado de Guerrero. La escama blanca del mango (EBM), Aulacaspis tubercularis Newstead, es una plaga emergente de importancia económica en México, debido a que daña el follaje y ramas de árboles de mango, así como la apariencia de frutos destinados a exportación y mercado nacional.  El objetivo del estudio fue conocer la distribución e intensidad de infestación de la plaga en los diferentes cultivares de mango de las regiones productoras del estado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…Monitoring of WMS on the cultivar 'Manila' has also been carried out in the states of Guerrero and Sinaloa, Mexico, however, the values reported correspond only to the annual average, therefore, it is not known in which season they presented the highest population. The maximum values detected in those states (0.12 -1.17 individual females and 0.05 -0.82 male colonies per leaf) are lower than those found in this study (Urías-López et al, 2016;Balderas-Palacios et al, 2017;Noriega-Cantú et al, 2017). Although differences were detected between orchards in the rate of male colonies/female individuals, the maximum values detected (0.67) are lower than the maximum values reported by Bautista-Rosales et al (2012) in the 'Ataulfo' cultivar, specifically in the April-June period (21-23 male colonies/female individuals).…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Monitoring of WMS on the cultivar 'Manila' has also been carried out in the states of Guerrero and Sinaloa, Mexico, however, the values reported correspond only to the annual average, therefore, it is not known in which season they presented the highest population. The maximum values detected in those states (0.12 -1.17 individual females and 0.05 -0.82 male colonies per leaf) are lower than those found in this study (Urías-López et al, 2016;Balderas-Palacios et al, 2017;Noriega-Cantú et al, 2017). Although differences were detected between orchards in the rate of male colonies/female individuals, the maximum values detected (0.67) are lower than the maximum values reported by Bautista-Rosales et al (2012) in the 'Ataulfo' cultivar, specifically in the April-June period (21-23 male colonies/female individuals).…”
Section: Discussioncontrasting
confidence: 71%
“…The studies have been carried out on the 'Manililla', 'Ataulfo', 'Manila', 'Tommy Atkins', 'Kent', and 'Keitt' cultivars. Among cultivars, 'Manila' has been reported to be more susceptible to the WMS, compared to other cultivars Balderas-Palacios et al, 2017;Noriega-Cantú et al, 2017). In Mexico, it has been reported that the WMS is concentrated more in the southern part of the tree and to a lesser extent in the western part of the tree.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations